Xilinx FPGA based three-phase PWM inverter and its application for utility connected PV system - Mekhilef, Saad; Rahim, N.A. (2002)
Analysis and practical implementation of the regular (symmetric, asymmetric) sampled three-phase PWM inverter waveform has been presented in this paper, which was digitally implemented on an Xilinx field programmable gate array FPGA. and the essential considerations involved in the feasibility of using a Xilinx XC4008E software-based to generate PWM. All the necessary Xilinx hardware/software techniques and programs required to implement and generate three-phase Pulse Width Modulation (PWM) are developed in detail, and demonstrated using practical results from an experimental Xilinx board. The techniques developed and presented in this paper are readily applicable to other currently available Xilinx chips.Simulation and hardware results of a new solar photovoltaic inverter configuration interconnected to the grid are presented. From the simulation and experimental results it is confirmed that the harmonic distortion of the output current waveform of the inverter fed to the grid is within the stipulated limits laid down by the utility companies.